Effects of Medium of Instruction (Yoruba Language) On Secondary School Students’ Performance in Mathematics (Global Journal of Human-Social Science, 2023)
Mathematics is one of the core subjects in secondary education and a good performance in the subject is a key to gaining admission into higher institution of learning In any mathematical educational setting the role of language cannot be deemphasized as it is a major tool that often determines the learning outcome of learners in the subject To this end the medium of instruction in mathematics classroom should be one that the learners can easily decipher This study therefore investigated the effects of mother tongue as supplementary medium of instruction on junior secondary school students performance in Mathematics in Ekiti State Nigeria The purpose was to examine the effectiveness of mother tongue as a supplementary medium of instruction The study adopted a three group pre-test post-test quasi experimental research design The sample for the study consisted of 194 junior secondary school one students selected from three secondary schools in Ekiti State through multistage sampling procedure One research instrument tagged Mathematics Performance Test was used for data collection in the study
Keywords: performance; mother tongue; instructional medium; mathematics